Influence of Choral Works of Russian Composers on the Development of Vocal and Musical Performance Abilities in Schoolchildren - Okhunjon Kimsanov; Saifiddin Annaev (Bright Mind Publishing, 2025)
Choral works by Russian composers play a significant role in developing students' vocal and musical performance abilities. These compositions, characterized by rich harmonies, expressive melodic lines, and deep emotional content, provide an excellent foundation for vocal training in school music education. The study examines how these works contribute to students’ vocal development, enhance their technical skills, and shape their artistic interpretation abilities. The research also explores the pedagogical aspects of using Russian choral music in music education, focusing on its effectiveness in fostering vocal expressiveness and ensemble skills. Furthermore, the study highlights the psychological and emotional impact of choral singing on students, emphasizing its role in building confidence, discipline, and a sense of musical collaboration. The findings suggest that incorporating Russian choral repertoire into school curricula significantly enhances students' vocal abilities and overall musicianship.
Keywords: Choral music, Russian composers, vocal development, musical performance, school music education, ensemble skills, artistic interpretation, pedagogical approaches, emotional impact, music appreciation.